3d Mapping Of Stiffness Evolution Of Hardening Concrete With Saps Using Elastic Wave Tomography - Eleni Korda; Nobuhiro Okude; Tomoki Shiotani; Geert De Schutter; Dimitrios G. Aggelis (e-Journal of Nondestructive Testing)
Phenomena occurring during the delicate phase of concrete curing can have a strong influence on the final mechanical properties. Therefore, monitoring the changes during hydration can provide meaningful information on the material properties. Lately, non-destructive techniques have received great attention for monitoring earlyage concrete. This paper aims to assess the ultrasonic velocity and stiffness development of hardening concrete during various curing stages using the Elastic Wave Tomography (EWT) technique. The monitoring of the curing process starts as soon as seven hours after casting and lasts up to seventy hours. A three-dimensional (3D) wave velocity map is created, and conventional concrete is compared to concrete containing SuperAbsorbent Polymers (SAPs), a novel admixture used for shrinkage mitigation by providing internal curing in the cementitious matrix. However, SAPs have been proven to reduce compressive strength when added to concrete, due to the increased porosity they induce. This porosity may also result in the reduction of the wave velocity. However, the internal curing provided by the SAPs can promote the formation of new hydration products in the matrix and thus (partly) compensate for the strength loss making the uniformity of the internal curing another important point of concern. EWT can provide global information on the homogeneity of the influence of the SAPs in the cementitious matrix as opposed to the wave velocity of a single wave path that is usually examined in practice. In addition, the determination of the early-age stiffness evolution can be connected to the final mechanical properties of the material. The dynamic Young’s Modulus is calculated and compared to the static Young’s modulus at 28 days. Predictions towards the static Young’s modulus are also made, showing good agreement.